PEMBERANTASAN BUTA AKSARA BERBASIS TUTORIAL TERPADU BAGI MASYARAKAT DESA PASIR ANGIN - La Ode Amril; Wilis Firmansyah; Yumi Hartati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Desa Pasir Angin Kec. Megamendung Kab. Bogor is one of the villages targeted to eradicate illiteracy to improve Literacy Rate (AMH) Kab. Bogor. Some of the causes of high illiteracy rates in the village of Pasir Angin are due to inaccessible education services, high cost, and low level of awareness and motivation for thecitizens. The integrated tutorial-based illiteracy eradication program is one of the alternative solutions for dealing with illiterate people in Pasir Angin Village. The implementation model of integrated illiteracy eradication based on integrated tutorial is the implementation of learning based on the integration between functional literacy education and family assistance. This means that after the residents learn to follow the learning along with the tutor then when the residents learn to go home the family contribute to participate mentoring. The illiteracyeradication program in Desa Pasir Angin was conducted for 12 July - 19 August 2017 at four different locations is Kp. Pasir Angin, Kp. Cikatapis, Kp. Cikatapis Wetan, and Kp. Setu with the number of participants as 91 residents. The results obtained are on the ability to read as many as 20 residents are in good category, 31 middle class citizens, and 40 people less category. Meanwhile, from the aspect of writing ability as many as 16 people in the good category, 26 middle class citizens, and 47 people less category. As for the ability to count as many as23 residents in either category, 35 middle class citizens, and 33 people less category.Keywords: Illiteracy, integrated tutorial, Pasir Angin village.